The Pathologic Role of Toll-Like Receptor 4 in Prostate Cancer - Ou, Tongwen; Lilly, Michael; Jiang, Wei (Frontiers in Immunology, 2018)
Toll-like receptor (TLR) 4 is expressed on normal and malignant prostate epithelial cells. The microbial TLR4 receptor and its downstream signaling pathways mediate innate immune responses in the host against invading pathogens. However, multiple lines of evidence shows that TLR4 expression is increased in prostate tissues from prostate cancer patients and altered TLR4 signals may promote cancer development, as well as anti-tumor effects. In this review, we have summarized key features of the TLR4 signaling pathway and its-associated immune responses and focused on the pathologic role of TLR4 in prostate carcinogenesis and tumor progression.